Settlement of Default Disputes in Construction Service Agreements in Decision Case Number 7/Pdt.G/2022/PN Toli-Toli - Siti Ruwaida Azzahra, Zahra (JURNAL MAHASISWA YUSTISI, 2025)
Disputes in construction service agreements often stem from defaults or failures to perform contractual obligations. This study examines the mechanism for resolving such disputes under Law Number 2 of 2017 concerning Construction Services, with reference to case Decision Number 7/Pdt.G/2022/PN Tli. The normative juridical method is applied through a case study approach. The research found that the default was due to the contractor's failure to fulfill construction obligations as agreed. The dispute resolution followed a litigation process after alternative dispute resolution attempts failed. The court ruled in favor of the plaintiff and imposed compensation on the defendant. The study highlights the importance of detailed contractual drafting, strengthening non-litigation dispute mechanisms, and increasing legal literacy among construction stakeholders..